PENGUKURAN KINERJA PERUSAHAAN BERDASARKAN BALANCE SCORECARD PADA PT ASURANSI MULTI ARTHA GUNA TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ahmad Sumarlan; Yulius Wahyu Setiadi (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2022)
Performance measurements that only focus on financial aspects often omit other aspects which are no less important. Such as, customer aspects, internal business process aspects, and learning and growth aspects. We need a tool that can measure performance from various aspects in a comprehensive manner, based on the conditions mentioned above, in order to achieve a comprehensive performance measurement, it is necessary to expand performance measures. One of the contemporary management tools that can measure performance in a balanced way is the balanced scorecard.Ã‚Â This study aims to determine whether or not the performance of the company PT. Asuransi Multi Artha Guna Tbk if measured using the balanced scorecard method. The type of research used in this research is descriptive design. The data collection technique used in this research is the documentation technique.Ã‚Â The data analysis technique uses descriptive analysis, which is an activity to compile, classify, interpret and interpret data so as to provide an overview of the problems faced or researched. The results of the balanced scorecard calculation show that the performance of PT. Asuransi Multi Artha Guna Tbk in 2017-2019 based on the four perspectives included in the pretty good category.Ã‚Â Keywords: Performance measurement, balance score cardÃ‚Â Ã‚Â